The expressions of NF-kb and TGFb-1 on odontoblast-like cells of human dental pulp injected with propolis extracts - Ira Widjiastuti; Ketut Suardita; Widya Saraswati (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Propolis is known to have beneficial effects, namely anti- bacterial, anti-viral, anti-inflammatory, antioxidant, and immunomodulatory. Propolis extracts with anti-inflammatory properties are expected to be useful in treating inflamed pulp tissue with a diagnosis of reversible pulpitis. The inflammation of pulp tissue is caused by bacteria, namely Lactobacillus acidophilus. This research used odontoblast like cells derived from pulp tissue of human third molars. Odontoblast like cells exposed to Lactobacillus achidophilus were used as a model of proinflammatory cytokine signaling. This research examined the effects of propolis extracts on odontoblast like cells exposed to Lactobacillus acidophilus. Purpose: This research was aimed to determine the effectiveness of propolis extracts on the activities of odontoblast-like cells exposed to Lactobacillus acidophillus by measuring the expressions of NFkb and TGF- b1. Methods: First, pulp odontoblast cultures were derived from human dental pulp tissues of impacted third molars removed by using digestion method. Next, odontoblast-like cells exposed to inactive Lactobacillus acidophilus bacteria were given propolis extract. Finally, the activities of odontoblast-like cells were monitored by measuring the expressions of NF-kb and TGFb-1 with immunocytochemistry technique. Results: A decline NF-kb expression and on increase of TGFb-1 expression on odontoblast like cells exposed to inactive Lactobacillus acidophilus. Conclusion: Propolis extracts inhibit the expression of NF-kb, and increase the expression of TGF-b1 in pulp odontoblast-like cells exposed to inactive Lactobacillus acidophillus.Latar belakang: Propolis dilaporkan mempunyai efek menguntungkan yaitu bersifat anti bakteri, anti virus, anti inflamasi, anti oksidan, dan imunomodulator. Ekstrak propolis dengan sifat anti inflamasi diharapkan bermanfaat untuk mengobati jaringan pulpa yang mengalami inflamasi dengan diagnosis pulpitis reversibel. Inflamasi jaringan pulpa disebabkan oleh bakteri diantaranya adalah Lactobacillus acidophilus. Pada penelitian ini digunakan Odontoblast like cells yang berasal dari jaringan pulpa dari gigi molar ke tiga manusia. Odontoblast like cells dipapar Lactobacillus acidophilus digunakan sebagai model signaling sitokin proinflamasi. Studi ini, meneliti pengaruh pemberian ekstrak propolis pada odontoblast like cells yang dipajan Lactobacillus acidophilus. Tujuan: Penelitian untuk mengetahui efektifitas ekstrak propolis terhadap aktifitas odontoblast like cells yang dipajan Lactobacillus acidophillus dengan mengukur ekspresi NF-kb dan TGF-b1. Metode: pembuatan kultur odontoblas pulpa berasal dari jaringan pulpa gigi Molar ke tiga impaksi yang dicabut menggunakan metode digesti. Odontoblast like cells dipajan bakteri Lactobacillus acidophilus inaktif, diberi ekstrak propolis dan aktifitas dari odontoblast like cells diukur melalui ekspresi NF-kb dan TGFb-1 secara imunositokimia. Hasil: Terjadi penurunan ekspresi NF-kb, dan peningkatan ekspresi TGFb-1 pada kultur odontoblas yang dipapar bakteri Lactobacillus acidophilus inaktif. Simpulan: Ekstrak propolis menghambat ekspresi NF-kb, dan meningkatkan ekspresi TGF-b1 pada odontoblast like cells pulpa yang dipajan bakteri Lactobacillus acidophillus inaktif